Self-powered, wireless-control, neural-stimulating electronic skin for in vivo characterization of synaptic plasticity. (January 2020) - Guan, Hongye; Lv, Dan; Zhong, Tianyan; Dai, Yitong; Xing, Lili; Xue, Xinyu; Zhang, Yan; Zhan, Yang
Abstract: Synaptic plasticity underlies brain changes when learning or memory takes place. Long-term memory requires modification of synaptic strengths between neurons. The characterization of the synaptic changes therefore reflects the long term storage of information in the brain structures. Traditionally, electrical neural-stimulating technique for characterizing synaptic plasticity requires external power source and steer-by-wire system. Here, a novel self-powered, wireless-control, neural-stimulating electronic skin (e-skin) for in vivo characterization of synaptic plasticity has been presented. The e-skin is composed of flexible photosensitive-triboelectric MAPbI3 /PDMS units. The outputting electrical neural-stimulating signal of the e-skin is generated by human body activities without any batteries, and the neural-modulation can be controlled by photo illumination on/off as wireless switch. To demonstrate the application of the e-skin in characterizing synaptic changes, we connect the device to the hippocampus of the mouse brain. The e-skin neural stimulating in the CA3 of mouse hippocampus and simultaneous recording field excitatory postsynaptic potentials (fEPSP) in the CA1 demonstrate that the e-skin can successfully elicit post-synaptic responses for in vivo characterization of synaptic plasticity. This self-powered photo-operate e-skin can provoke a new research direction for realizing battery-free, wireless-control, electrical neural-stimulating systems with implications in biomedical engineering and neural science. Graphical abstract: A novel self-powered, wireless-control, neural-stimulating electronic skin (e-skin) for in vivo characterization of synaptic plasticity has been presented. The outputting electrical neural-stimulating signal of the e-skin is generated by human body activities without any batteries, and the neural-modulation can be controlled by photo illumination on/off as wireless switch. The e-skin neural stimulating in the CA3 of mouse hippocampus and simultaneous recording field excitatory postsynaptic potentials (fEPSP) in the CA1 demonstrate that the e-skin can successfully elicit post-synaptic responses for in vivo characterization of synaptic plasticity. Image 1 Highlights: A novel self-powered and wireless-control e-skin can in vivo characterize synaptic plasticity. The e-skin can realize neural stimulation in hippocampus without battery. The e-skin can elicit post-synaptic responses for in vivo characterization of synaptic plasticity. The neural stimulation is adjusted by photo-illumination as a wireless-contol technique.